2019
DOI: 10.1177/2045125319891386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ECG abnormalities and risk factors for QTc interval prolongation in hospitalized psychiatric patients

Abstract: Background: Psychiatric patients are at risk of cardiovascular diseases, and many psychotropic drugs can prolong QTc interval. Requirements for electrocardiogram (ECG) monitoring have been set up in our psychiatric university hospital. The objective of this study was to determine the proportion of adult patients who had an ECG during their hospitalization, the prevalence of ECG abnormalities, the evolution of the QTc after admission, and the risk factors for QTc prolongation. Methods: Retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
4
5
3
1
Order By: Relevance
“…Although the antiemetic regimen used in our study may not be the standard practice at other sites, the findings provide clinically significant information regarding the safety of drug combinations with potential QT-prolonging effects. QTc changes with time were significant in females and elderly in our study; this is in agreement with the findings of a retrospective ECG review of hospitalized psychiatry patients on psychotropic drugs 18 . The gender difference is likely to be sex hormone-related 19 whereas the age difference is likely to be due to the effect of ageing on the myocardium and autonomic tone 20 ; interestingly, the latter study showed that in elderly, the QTc prolongation is more severe in males compared with females.…”
Section: Discussionsupporting
confidence: 92%
“…Although the antiemetic regimen used in our study may not be the standard practice at other sites, the findings provide clinically significant information regarding the safety of drug combinations with potential QT-prolonging effects. QTc changes with time were significant in females and elderly in our study; this is in agreement with the findings of a retrospective ECG review of hospitalized psychiatry patients on psychotropic drugs 18 . The gender difference is likely to be sex hormone-related 19 whereas the age difference is likely to be due to the effect of ageing on the myocardium and autonomic tone 20 ; interestingly, the latter study showed that in elderly, the QTc prolongation is more severe in males compared with females.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, a higher risk of QTc prolongation was observed in male patients; however, this result is inconsistent with some other studies 17,18 . This inconsistency may be due to the differences in the race of the patients included in the research.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, a higher risk of QTc prolongation was observed in male patients; however, this result is inconsistent with some other studies. 17,18 This inconsistency may be due to the differences in the race of the patients included in the research. On the other hand, our result confirmed the finding of an epidemiological survey based on a Chinese population, which suggested that men were more likely to have QTc prolongation (QTc > 450 ms for men and QTc > 470 ms for women).…”
Section: Discussionmentioning
confidence: 99%
“…And these drugs were classified into three categories, “known risk,” “possible risk,” or “conditional risk” of TdP. In our study, comparisons were conducted with the QT drug lists of CredibleMeds ® in an attempt to identify drugs with a potential risk of TdP that are not on the list ( 25 ).…”
Section: Methodsmentioning
confidence: 99%